Effect of pH, Amount of Metal Precursor, and Reduction Time on The Optical Properties and Size of Zinc Oxide Nanoparticles Synthesized Using Aqueous Extract of Rhizomes of Acorus calamus - Tamang, Melina; Sapkota, Kamal Prasad; Shrestha, Sabita (Journal of Nepal Chemical Society, 2024)
Nanoparticles possess various unique characteristics compared to the corresponding bulk materials. Large band gap, non-toxic nature, and multi-applicability are the worthwhile characteristics of zinc oxide to be synthesized and studied. The size of nanoparticles can be controlled by varying the different experimental conditions. This paper reports the synthesis of zinc oxide nanoparticles by using an aqueous extract of rhizomes of Acorus calamus, where the bio-components present in aqueous extract acted as reducing agents. The size and band gap energy of zinc oxide nanoparticles were studied by varying different parameters such as pH, concentration of the metal precursor, and reduction time. The variations in the size of nanoparticles were studied by UV-visible spectroscopy. FTIR showed phenolic compounds, primary amines, and amides (proteins/enzymes) as the functional groups responsible for the reduction of metal precursors to form nanoparticles. The surface morphology of nanoparticles was studied by FE-SEM image. The FE-SEM image displayed the formation of various shapes and agglomeration of the nanoparticles. XRD pattern revealed that the average size of zinc nanoparticles is 10 nm. In vitro antibacterial activity of ZnO nanoparticles has been assayed against gram-positive and gram-negative bacteria. The growth inhibitory activity of nanoparticles against different bacterial pathogens has also been determined